2010
DOI: 10.1088/0266-5611/26/12/125008
|View full text |Cite
|
Sign up to set email alerts
|

An adjoint field approach to Fisher information-based sensitivity analysis in electrical impedance tomography

Abstract: An adjoint field approach is used to formulate a general numerical framework for Fisher information-based sensitivity analysis in electrical impedance tomography. General expressions are given for the gradients used in standard least-squares optimization, i.e. the Jacobian related to the forward problem, and it is shown that these gradient expressions are compatible with commonly used electrode models such as the shunt model and the complete electrode model. By using the adjoint field formulations together wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
0
13
0
Order By: Relevance
“…where Jδθ, ξ d = δθ, J * ξ , see also [10][11][12]16]. Based on the scalar product (10), the negative loglikelihood function (7) can now be written…”
Section: Maximum Likelihood and The Truncated Svdmentioning
confidence: 99%
See 4 more Smart Citations
“…where Jδθ, ξ d = δθ, J * ξ , see also [10][11][12]16]. Based on the scalar product (10), the negative loglikelihood function (7) can now be written…”
Section: Maximum Likelihood and The Truncated Svdmentioning
confidence: 99%
“…where I + denotes a truncated pseudoinverse of the Fisher information I, which is based on the singular value decomposition (SVD), see also [10,11,17]. It can be readily shown that the regularized maximum likelihood solution (18) is equivalent to a regularized pseudoinverse based directly on the linearized operator problem…”
Section: Maximum Likelihood and The Truncated Svdmentioning
confidence: 99%
See 3 more Smart Citations